THE EFFECT OF DIGITAL LITERACY AND E-COMMERCE UTILIZATION ON MSME PERFORMANCE IN BATAM CITY - Herman, Hendri; Luran, Muhammad Fadli; Muhidin, Deden (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study aims to analyze the effect of digital literacy and e-commerce utilization on the performance of Micro, Small and Medium Enterprises (MSMEs) in Batam City. Digital literacy is an individual's ability to understand, manage, and utilize information technology effectively in supporting business activities. On the other hand, e-commerce has become a strategic tool that helps MSMEs reach a wider market, improve operational efficiency, and strengthen competitiveness. This research is motivated by the rapid development of technology and the need for MSMEs to adapt to the digital era. The object of this research is MSMEs in Batam city with a sample size of 71 MSMEs. The research data were obtained with the help of questionnaire distribution. The data is processed using the SPSS application. The results of the study are partially digital literacy and ecommerce utilization have a significant effect on MSME performance. Simultaneously, digital literacy and e-commerce utilization have a significant effect on the performance of MSMEs in Batam city. From the results of this study, it is hoped that MSME players can adopt digital in an effort to increase the benefits obtained.